Hubungan Kemandirian Dengan Nilai Glukosa Darah Penderita DM Tipe 2 Di Puskesmas Kamoning - Istibsaroh, Faridatul; Qomariya, Nurul; Mawardi, Elok Alfiah; Sugiyanto, Jatim; Arif, Ahmad Zaini (Indonesian Journal of Professional Nursing, 2024)
Diabetes mellitus is a disease characterized by increased blood glucose levels, which can cause various complications, including damage to blood vessels, heart, kidneys, and increase the risk of stroke and death. Type 2 diabetes mellitus is caused by insulin retention in muscle and liver cells, which ultimately interferes with the ability of pancreatic beta cells to produce insulin, so that glucose cannot enter the body's cells. The purpose of this study was to analyze the relationship between independence and blood glucose values ​​in patients with type 2 diabetes mellitus in the Kamoning Health Center work area. The design of this study was a quantitative cross-sectional approach with a population of all type 2 diabetes mellitus patients at the Kamoning Health Center of 55 people. Samples were taken using a purposive sampling technique, with a total of 48 patients. The instruments used were the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire and the Easy Touch GCU blood glucose measuring device. The results showed that out of 48 respondents, 20 patients (41.7%) had controlled glucose values ​​with good self-care, while 1 patient (2.1%) had controlled glucose values ​​with poor self-care. On the other hand, 15 patients (31.2%) had uncontrolled glucose levels despite good self-care, and 12 patients (25%) had uncontrolled glucose levels with poor self-care. The Chi Square test showed a p value = 0.006, indicating a relationship between independence and blood glucose values. The conclusion of this study is that there is a relationship between independence and blood glucose values ​​in patients with type 2 diabetes mellitus. Good self-care behavior and routine monitoring of blood glucose values ​​are very important to control glucose values ​​and prevent further complications.